Thermoelectric properties of polycrystalline Bi₁₋ₓSbₓ solid solutions in the concentration range x = 0 – 0.25 - Doroshenko, A. N.; Rogacheva, E. I.; Drozdova, A. A.; Martynova, K. V.; Men'shov, Yu. V. (National Academy of Sciences of Ukraine, 2016)
A detailed investigation of the dependence of thermoelectric properties of polycrystalline Bi₁₋ₓSbₓ solid solutions on composition in a wide concentration range (x = 0 – 0.25) was performed at room temperature. The objects of study were cast samples of various composition obtained by ampoule method in one technological cycle consisting in cooling of ampoules with melts in the air and subsequent long homogenizing annealing at temperature (520 ± 5) K for 720 hours. It was shown that the composition dependences of properties are of clearly expressed nonmonotonic type. The presence of concentration anomalies of thermoelectric properties was confirmed that had been earlier observed in the range x = 0 – 0.1 on cast samples after different kinds of thermal treatment and interpreted as manifestation of electron phase transitions. A complicated nature of dependences at x > 0.1 is attributable to qualitative changes in Bi₁₋ₓSbₓ band structure at certain critical compositions, a change in relative contribution to conductivity of charge carriers from different energy bands with a change in antimony concentration and high sensitivity of energy spectrum and physical properties of Bi₁₋ₓSbₓ к to external effects.
Keywords: bismuth-antimony solid solution; composition; thermoelectric properties; electronic transition; critical phenomena